Similar patient positioning: A key factor in follow-up studies when using model-based radiostereometric analysis of the hip. Issue 2 (May 2020) - Lindgren, L.; Jørgensen, P.B.; Mørup, R.M.S.; Jensen, M.; Rømer, L.; Kaptein, B.; Stilling, M.
Abstract: Introduction: Despite protocols, patients are not positioned exactly alike at radiostereometric (RSA) follow-up examinations, and it is unknown how much variation is tolerable. We report precision for optimal and extreme position differences from a phantom hip-study, and clinical precision of hip-RSA. Methods: A femoral stem with 3 bead-towers was fixed in a saw bone with bone-markers (phantom), and series of RSA examinations within optimal (5 × 5 cm and 5°) and extreme (20 × 30 cm and 30°) phantom positions were obtained. Double-examination RSA of 12 patients with the same femoral stem type were analyzed. Both model-based (CAD) and marker-based (MM) analysis was used. Precision was reported as standard deviation of differences. Results: Precision for translations in the optimal and extreme phantom position were below 0.06 mm and 0.02 mm for MM analysis, and below 0.05 mm and 0.18 mm for CAD analysis, respectively. Precision for rotations in the optimal and extreme phantom rotation were below 0.18° and 0.26° for MM analysis, and below 0.34° and 0.52° for CAD analysis, respectively. Clinical precision was 0.29 mm and 0.44° for MM analysis, and 0.40 mm and 1.59° for CAD analysis. Conclusion: Extreme differences in patient position during RSA examination negatively affects precision, and CAD model-analysis was more sensitive than MM analysis. Longitudinal translation and rotation about the long stem-axis are the effect parameters which are most affected by position and rotation changes, and also the best indicators of implant loosening. Implications for practice: Based on our research, we recommend that similar patient positioning between follow-up RSA examinations is debated and prioritized.